PRIMARY IMMUNODEFICIENCY: STATUS OF A PROBLEM TODAY. RUSSIAN NETWORK OF JMF-CENTERS - E. A. Latysheva ("Paediatrician" Publishers LLC, 2013)
The problems of primary immunodeficiency in Russia and the ways of solving of them are discussed in the article. Primary immunodeficiency is a group of rare diseases, so awareness of this pathology in the medical community and among patients is very low. This leads to late diagnosis and inadequate treatment of patients with such conditions. The result of the late beginning of treatment is early development of disability, and the high mortality rate of patients, as well as the high costs of the treatment of complications of primary immunodeficiency and sick-leave certificates for the government. Today in time and adequate therapy allows patients not only to reach adulthood without signs of disability, and to lead an active way of life, but to have healthy children. Given the high cost of therapy in many countries, the issue of providing patients with life-saving drugs remains unresolved. The global practice is to involve social organizations and funds. One of the foundations supporting educational programs, development of laboratories and research in the field of primary immunodeficiency is the Foundation of the Jeffrey Modell. A network of centres for primary immunodeficiency supported by the Jeffrey Modell Foundation (JMF-centers) has started its functioning over the territory of the Russian Federation since 2011 in order to improve diagnostics and treatment of patients with primary immunodeficiency. A brief description of activity of these centers is presented in the article.